Single ventricle transthoracic echocardiography study - José Abreu Cruz; Ana M. Álvarez Ruiz; Saúl Armenteros Terán; Rogelio Romero Millares (ECIMED, 2014)
The single ventricle occurs in 1 x 6 500 births. It is associated with the transposition of great vessels and also with lung stenosis, among others. The clinical picture depends on the coexistent anomaly. Echocardiography 2-D (from apical approximation) was used to show the absence of intraventricular septum and rudimentary chamber in a 38 year old man, who was cyanotic since birth. The single ventricle is confirmed by angiocatheterism.